Arabic verb patterns and macrostructure in adolescent narratives: A comparative analysis across writing systems - Tallas-Mahajna, Naila; A. Elhija, Dua (East European Journal of Psycholinguistics, 2025)
The aim of the study is to explore verb patterns within narrative structures among Arabic-speaking adolescents using different writing systems—Arabic script, Romanized Arabic, and Hebrew script. It examines how these scripts influence the complexity and variety of verb usage, highlighting linguistic challenges in a multilingual educational context. Method: Analyzed narratives from 78 students across three grade levels (7th, 9th, and 11th) using a mixed-methods approach. This included evaluating narrative macrostructure and analyzing verb usage, focusing on frequency, type, and token. Verbs were categorized by semantic features such as agentivity, transitivity, and tense to understand their role in narrative construction across different scripts. Results: Hebrew script users displayed more complex verb patterns and higher macrostructural scores compared to peers using Arabic or Romanized Arabic scripts. There was a significant positive correlation between the diversity of root types used in Arabic script and narrative complexity, highlighting the impact of linguistic depth on narrative quality. A preference for eventive and transitive verbs was observed across all writing systems, with past tense verbs predominantly influencing narrative structuring. Conclusions: Writing system choice significantly impacts narrative verb patterns in a diglossic environment. Hebrew script is less cognitively demanding, suggesting the need for educational strategies to enhance narrative skills and support linguistic adaptability across scripts in multilingual settings.Disclosure Statement The authors reported no potential conflicts of interest.